Wind energy the unseen force. Part 2 - Hoffman, Anne; Seibold, Jorg (Virginia : Landmark Media Inc., 2001)
This industry quite literally goes whichever way the wind blows. Of all the renewable energy sources, moving air is the most volatile. Sometimes, the turbines have to make do with a gentle breeze and, at other times, fight against a raging gale. And wind energy scatters opinions like no other. Politicians, energy producers, environmentalists and ordinary citizens all have differing views
English language producer, K. Michael Tikhomerov ; English language director, Rick Bluett ; video editor, Hartmut Altenpohl ; camera, Christian Dransfeld, Michael Zausch ; executive producers, Arno Hefner, Klaus-Dieter Seelig
DVD format
Keywords: Energy consumption; Wind power; Renewable energy resources; Wind turbines; Wind power -- History -- Germany